2019
DOI: 10.1136/bmjopen-2018-027895
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of self-rated health among older adults: a comparison of China and the United States

Abstract: ObjectivesWe used nationally representative samples of China and the US older population to investigate (1) whether factors influencing self-rated health among older Chinese were similar to those among older Americans; and (2) whether there was a significant cross-national difference in self-rated health between China and the USA after controlling those available influencing factors.DesignA cross-sectional study. Data came from the 2014 Health and Retirement Study and China Health and Retirement Longitudinal S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
(18 reference statements)
5
30
0
Order By: Relevance
“…Without this awareness and affordability, they regard themselves as healthy instead. In addition, SRH is related to many other factors, such as chronic disease, outdoor activities, and depression, not just ADL ability [34]. In other words, even if some older people with more education have bad or fair SRH, they may have other problems but still have good functional ability, according to these six items.…”
Section: Resultsmentioning
confidence: 99%
“…Without this awareness and affordability, they regard themselves as healthy instead. In addition, SRH is related to many other factors, such as chronic disease, outdoor activities, and depression, not just ADL ability [34]. In other words, even if some older people with more education have bad or fair SRH, they may have other problems but still have good functional ability, according to these six items.…”
Section: Resultsmentioning
confidence: 99%
“…Positive self-perceived health was also associated with high cognitive status, functional independence and less depressive symptoms in a study conducted by Krug et al ( 90) in a regional sample of older Brazilians. Maintained functional capacity was the variable with the greatest explanatory potential for self-rated health, according to microdata from the National Health Survey (2013), conducted by Figueiredo et al In a comparative study conducted by Xu et al (2) with data from HRS and CHARLS, the authors found that 78% of older adults in China reported fair or poor health status, whereas almost 74% of older adults in the USA reported it as excellent, very good or good. However, older individuals who reported more limitations in activities of daily living, worse self-reported memory, worse mental health, and chronic health conditions had worse self-rated health in both countries.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that healthcare policies must be devised to play an important role in reducing social inequalities in healthcare in Brazil and in Portugal, with planning that guarantees care for vulnerable populations, including that of older adults. This can be accomplished: (1) through greater investments in the area of primary care; (2) through the reorganization of mental healthcare services for easier access by older adults; (3) by expanding the dissemination of good healthcare practices, with home visits by healthcare professionals particularly in the most vulnerable communities; and (4) by ensuring that everyone has access to free services, based on principles of equity and solidarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations